Increased folding and channel activity of a rare cystic fibrosis mutant with CFTR modulators - Caldwell, Ray A. (American Physiological Society, 2011)
Cystic fibrosis (CF) is a lethal recessive genetic disease caused by mutations in the CFTR gene. The gene product is a PKA-regulated anion channel that is important for fluid and electrolyte transport in the epithelia of lung, gut, and ducts of the pancreas and sweat glands. The most common CFTR mutation, ΔF508, causes a severe, but correctable, folding defect and gating abnormality, resulting in negligible CFTR function and disease. There are also a large number of rare CF-related mutations where disease is caused by CFTR misfolding. Yet the extent to which defective biogenesis of these CFTR mutants can be corrected is not clear. CFTRV232D is one such mutant that exhibits defective folding and trafficking. CFTRΔF508 misfolding is difficult to correct, but defective biogenesis of CFTRV232D is corrected to near wild-type levels by small-molecule folding correctors in development as CF therapeutics. To determine if CFTRV232D protein is competent as a Cl(−) channel, we utilized single-channel recordings from transfected human embryonic kidney (HEK-293) cells. After PKA stimulation, CFTRV232D channels were detected in patches with a unitary Cl(−) conductance indistinguishable from that of CFTR. Yet the frequency of detecting CFTRV232D channels was reduced to ∼20% of patches compared with 60% for CFTR. The folding corrector Corr-4a increased the CFTRV232D channel detection rate and activity to levels similar to CFTR. CFTRV232D-corrected channels were inhibited with CFTR(inh-172) and stimulated fourfold by the CFTR channel potentiator VRT-532. These data suggest that CF patients with rare mutations that cause CFTR misfolding, such as CFTRV232D, may benefit from treatment with folding correctors and channel potentiators in development to restore CFTRΔF508 function.